2019
DOI: 10.1016/j.applthermaleng.2018.10.126
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic performance and stress analysis of the steam generator of parabolic trough solar power plants

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…González‐Gómez et al modeled the power block transient performance as a series of steady‐state simulations of different loads; however, the heat exchangers in the steam generator system were modeled by coupled transient thermodynamic and stress models to compute the stress. [ 31 ] The analytical stress models were discussed for the critical points of the heat exchanger, and a finite element simulation was compared with the analytical model. Cenuşă et al presented a model to calculate exergy destruction during the heat transfer period in a steam generator.…”
Section: Steady‐state Characteristics Analyses Of Cspmentioning
confidence: 99%
See 1 more Smart Citation
“…González‐Gómez et al modeled the power block transient performance as a series of steady‐state simulations of different loads; however, the heat exchangers in the steam generator system were modeled by coupled transient thermodynamic and stress models to compute the stress. [ 31 ] The analytical stress models were discussed for the critical points of the heat exchanger, and a finite element simulation was compared with the analytical model. Cenuşă et al presented a model to calculate exergy destruction during the heat transfer period in a steam generator.…”
Section: Steady‐state Characteristics Analyses Of Cspmentioning
confidence: 99%
“…González‐Gómez conducted the start‐up simulations and some results are shown in Figure 8 , including the oil‐to‐steam generation temperature, mass flowrate, turbine power output, and evaporator performance. [ 31 ] To avoid thermal shock in the pipeline, oil is sent to the evaporator at 260 °C, which is 20 °C above the saturation temperature of water in the drum. The start‐up of the steam generator takes 45 min and requires ≈36.4 MWh.…”
Section: Dynamic Characteristics Analyses and Control Strategiesmentioning
confidence: 99%
“…In an NGCC plant, the thick-walled high pressure (HP) drum is one of the most vulnerable components that can suffer from the fatigue damage due to the load-following operation. One way of computing the fatigue damage is through the development of a detailed finite element method (FEM) model of stress distribution in the drum. , However, FEM models are computationally expensive, and therefore, dynamic optimization of the plant operation using the FEM model coupled with the plant-wide model is likely to be computationally intractable.…”
Section: Introductionmentioning
confidence: 99%
“…The thermomechanical stress was calculated considering the notch effect using EN 12952-3. Taler et al , and González-Gómez et al , used both EN 12952-3 and FEM to calculate the drum stress at the drum/downcomer junctions. They observed that other than the specific location at the drum/downcomer junctions that EN 12952-3 already accounts for, there can be additional locations at the drum/downcomer junctions where stress concentration should be evaluated during the start-up process.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed an increase up to 40% of the operational and maintenance costs of a conventional 400 MWe thermal plant, in the case of high penetration of variable renewable energies. González-Gómez et al [18,19] analyzed the dynamic performance and the lifetime of the SG of a parabolic trough power plant. The creep damage was neglected due to the low working temperatures of the SG.…”
mentioning
confidence: 99%